A series of soluble thieno-fused coronene nanoribbons of precise lengths - Yang, Xuan; Elbert, Sven; Rominger, Frank; Mastalerz, Michael (Journal of the American Chemical Society, 2022)
Among graphene nanoribbons (GNRs), reports on coronene-based GNRs were very rare, despite the unique optoelectronic properties of coronene. Herein, the synthesis of a series of structurally precise and soluble thieno-fused coronene nanoribbons (CR-1 to CR-4) with up to four coronene units connected through benzene rings along their K-regions is described by two different synthetic approaches. Due to the triptycene end-caps, all CRs are soluble, allowing the characterization of such structures in solution and the study of the length-dependent photophysical properties that are supported by theoretical calculations.
Gesehen am 13.07.2022